Analisis Kepemimpinan Transformasional terhadap Akuntabilitas Laporan Keuangan Pondok Pesantren - Hardana, Ali (Penerbit Goodwood, 2023)
Purpose: The Accountability of Islamic boarding schools in terms of transparency cannot yet be assessed as optimal, efficient and effective. The formulation of the problem that occurs is whether trust and transformational leadership affect the accountability of the financial reports of the Darul Istiqomah Hutapadang Islamic Boarding School. The purpose of this study was to determine the effect of trust and transformational leadership on the accountability of financial reports at Darul Istiqomah Hutapadang Islamic Boarding School. Methodology/approach: The research method used in this study was to use quantitative methods with multiple linear regression analysis using descriptive statistics, validity test, reliability test, normality test, classical assumption test, multicollinearity test, heteroscedasticity test, hypothesis test and multiple linear regression analysis test to obtain the results of the study used the SPSS version 26 application, the data used in this study were primary data obtained directly from the answers of 30 respondents who were teachers and staff of the Islamic boarding school office. Results/findings: The results of the study show that the variable of trust has a partial effect on accountability and transformational leadership partially has no effect on accountability. Simultaneously the variables of trust and transformational leadership influence accountability. Limitations: Ownership structure and ownership has no relationship with debt policy Contribution: Indri Ayu Lestari (2022) The results of this study indicate that Foreign Institutional Ownership, Domestic Institutional Ownership, and Dividend Policy have a positive and significant effect on Firm Value. Foreign Institutional Ownership has a negative and significant effect on Dividend Policy. Domestic Institutional Ownership has no effect on Dividend Policy. Dividend Policy as an intervening variable is unable to mediate Foreign Institutional Ownership of Firm Value. Dividend Policy as an intervening variable is unable to mediate Domestic Institutional Ownership of Firm Value.